ALTERED ARTERIAL DOPPLER FLOW PATTERN AND PERINATAL OUTCOME IN INTRAUTERINE GROWTH RESTRICTION - Nayak, Krishnananda; Kumar, Pratap; Shetty, Ranjan; Shetty, Kiran; Jyothi; Lewis, Leslie Edward; Maiyya, Shreemathi S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: Intrauterine growth restriction (IUGR) is one of the common conditions that interfere with the growth of the fetus accounting for 10-15% of pregnant woman. Literature explores a wide range of incidence of perinatal complication including mortality among IUGR pregnancies. Limited data available on these complications confined to coastal Karnataka and its association with abnormal arterial Doppler flow pattern. To study the perinatal complications associated with IUGR pregnancies and its prevalence in comparison to healthy controls of comparable gestational age. Methods: This cohort study screened 53 IUGR fetuses by an antenatal scan at gestational age of 27 weeks or more. The diagnosis of IUGR was made according to established criteria from SOGC clinical practice guidelines August 2013. The data also included 48 appropriate for gestational age fetuses with healthy mothers with the comparable gestational week. Experienced cardiac sonographer and gynecologist performed fetal echocardiography (ECHO) using Vivid 7, GE health-care system ECHO machine with the convex transducer of frequency 1.7-2.4 MHz. The study was conducted at south Indian tertiary care center. Results: This study included 53 IUGR cases and 48 non-IUGR controls. The mean age was 27±4.37 and 26.88±3.14 years in IUGR and non-IUGR groups, respectively. Fetal Doppler study variables showed a significant decrease in peak aortic velocity and velocity time integral which was not evident on other valves, though mitral antegrade flow during atrial contraction was found to be lower among IUGR group. In two-dimensional chamber quantification of IUGR group revealed significant increase in pulmonary artery dimension, right ventricular (RV) dimension and RV thickness than the control group (p<0.05). The anthropometric parameters such as weight and length; abdomen circumference was significantly lower in IUGR group, whereas head circumference found to be more in IUGR group (p<0.001). The gestational weeks at delivery was significantly different among two groups with IUGR group depicting the early delivery group. p<0.001(35.58±2.92 and 38.5±0.96 in IUGR and non-IUGR groups, respectively). IUGR group also had prolonged neonatal intensive care unit stay when compared to controls (p<0.001). Conclusions: IUGR carries profound course in altered Doppler indices and cardiac function which explore its prediction on mortality and adverse perinatal outcome. This study showed significant perinatal mortality accounting for 5.6% among IUGR cases when compared to normal. Although tissue Doppler indices show normal variants, IUGR possesses significant adverse perinatal outcome, however with lesser incidence compared to severe form of IUGR subsets who show altered tissue annular velocities. Keywords: Intrauterine growth restriction, Echocardiography, Doppler, Perinatal.